2009
DOI: 10.1248/bpb.32.921
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Modeling and Prediction of Plasma Pyrrole-Imidazole Polyamide Concentration in Rats Using Simultaneous Urinary and Biliary Excretion Data

Abstract: Pharmacokinetic (PK) modeling has been proposed as a means to improve the efficiency of drug development. It is difficult to develop an appropriate pharmacokinetic model if the lower limit of quantification (LLOQ) of the assay of the plasma drug concentration is high. The mathematical method of determining the plasma drug concentration below the LLOQ was discussed previously. 1,2) The method of analyzing the data including the urine concentration to construct the PK model that cannot be constructed using only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Efforts of Nagashima et al established that Py-Im polyamides of different architecture were detectable in rat serum several hours after intravenous (i.v.) administration (12). Matsuda et al further showed that a Py-Im polyamide targeted to the TGF-β1 promoter affected target gene expression in vivo (rat renal cortex) without evidence of systemic toxicity (13,14).…”
mentioning
confidence: 99%
“…Efforts of Nagashima et al established that Py-Im polyamides of different architecture were detectable in rat serum several hours after intravenous (i.v.) administration (12). Matsuda et al further showed that a Py-Im polyamide targeted to the TGF-β1 promoter affected target gene expression in vivo (rat renal cortex) without evidence of systemic toxicity (13,14).…”
mentioning
confidence: 99%
“…Previous reports have shown that PI polyamides are not absorbed from the intestine [133]. After transvenous distribution in rat organs, PI polyamides were excreted into urine and bile without any metabolism [133,134].…”
Section: Development Of Novel Drugsmentioning
confidence: 99%
“…Previous reports have shown that PI polyamides are not absorbed from the intestine [133]. After transvenous distribution in rat organs, PI polyamides were excreted into urine and bile without any metabolism [133,134]. Matsuda et al showed that PI polyamides accumulated in nuclei of kidney cells in rats and were maintained for about two weeks without any drug delivery system [135,136].…”
Section: Development Of Novel Drugsmentioning
confidence: 99%
“…The LLOQ was determined as 1 µg/mL for both PI polyamides A and B. All of the methods were successfully applied to evaluate the pharmacokinetics of the PI polyamides (Fukasawa et al, 2009;Fukasawa et al, 2007;Nagashima et al, 2009b Intra-assay Inter-assay Matrix Table 1. Intra-and inter-assay accuracy and precision for the determination of PI polyamides A and B in rat plasma and urine.…”
Section: Bioanalyticsmentioning
confidence: 99%
“…To predict the effective dose of PI polyamide B in Dahl-S rats administered at 1 mg every 2 or 3 days for 4 weeks, pharmacokinetic simulations of PI polyamide B were performed using a slightly modified pharmacokinetic model (Nagashima et al, 2009b) by NONMEM program. The average plasma concentrations of PI polyamide B after the administration at 1 mg every 3 and 2 days were 0.18 and 0.28 µg/mL, respectively, which were calculated by the area under the concentration-time curves between 0 and 27 days, divided by 27 days.…”
Section: Pharmacokinetic Modeling With Excretion Data In Addition To mentioning
confidence: 99%